Strategies for effective implementation and scale-up of a multi-level co-designed men's health initiative “Sheds for Life” in Irish Men's Sheds - McGrath, Aisling; Richardson, Noel; Murphy, Niamh (Frontiers in Health Services, 2022)
Sheds for Life is a gender-specific tailored men’s health initiative engaging ‘hard-to-reach’ men in the Men’s Shed setting in Ireland. It is implemented by multiple stakeholders at individual, provider, organization and systems level and thus multiple contextual factors influence its scalability. This research used established implementation science frameworks to guide participatory research approaches that captured the process and identified facilitators of and barriers to implementation and scale-up. Active recruitment, co-design processes, leadership and stakeholder engagement emerged as key facilitators of implementation. Prominent barriers were institutional capacity and funding. Acceptability, adoption and appropriateness of the initiative were high among stakeholders with sustainability largely contingent on funding and staff resources. Findings make a valuable contribution to knowledge by capturing the process involved in the implementation of a complex multi-level men’s health intervention. It provides a ‘how to’ guide of strategies to engage hard-to-reach men with health promotion, the operationalization and application of implementation frameworks in community-based health promotion, and the implementation of health promotion in Men’s Sheds. Documented barriers and facilitators that impact implementation of a community-based men’s health program are rare and provide a valuable blueprint for practitioners, researchers and policy makers in the field.